Does customer who defends our brands tends to be loyal? - Muhammad Dino Putra Nurcahya; Chairy Chairy (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This Study is to examine whether customer who tend to defend the brands, often called advocacy tend to be loyal or not. This study proposes the extention of previous study. The Previous study using situational Brand Engagement which consist of Affective, Cognitive, And Behavior to strengthen the Advocacy and to examine the influence of advocacy to form loyal customer. In Order to test the relationship within the variable accurately and reliably, A questionnaire was developed and distributed to 350 retail bank customer who are SME merchant of which 203 valid responses were returned to the researcher. The Questionnaire were done using existing scales from previous literature about situational brand engagement and advocacy. Partial Least Square Structural Equational Modeling (PLS-SEM) were used for this study.The result are Affective, Cognitive, and Behavior impact to Advocacy significantly, but advocacy impact to loyalty not significantly, this is contrast from previous research that state whether strong advocate consumer tends to be loyal. The other results and implications are summarized in the discussion part of the paper in which recommendation are provided.